Lipoxin A4 stimulates endothelial miR‐126–5p expression and its transfer via microvesicles. Issue 5 (18th January 2017) - Codagnone, Marilina; Recchiuti, Antonio; Lanuti, Paola; Pierdomenico, Anna Maria; Cianci, Eleonora; Patruno, Sara; Mari, Veronica Cecilia; Simiele, Felice; Di Tomo, Pamela; Pandolfi, Assunta; Romano, Mario
ABSTRACT: The proresolution lipid mediator lipoxin (LX)A4 bestows protective bioactions on endothelial cells. We examined the impact of LXA4 on transcellular endothelial signaling via microRNA (miR)‐containing microvesicles. We report LXA4 inhibition of MV release by TNF‐α‐treated HUVECs, associated with the down‐regulation of 18 miR in endothelial microvesicles (EMVs) and the up‐regulation of miR‐126–5p, both in HUVECs and in EMVs. LXA4 upregulated miR‐126–5p by ∼5‐fold in HUVECs and promoted a release of microvesicles (LXA4 ‐EMVs) that enhanced miR‐126–5p by ∼7‐fold in recipient HUVECs. In these cells, LXA4 ‐EMVs abrogated the up‐regulation of VCAM‐1, induced in recipient HUVECs by EMVs released by untreated or TNF‐α‐treated HUVECs. LXA4 ‐EMVs also reduced by ∼40% the expression of SPRED1, which we validated as an miR‐126–5p target, whereas they stimulated monolayer repair in an in vitro wound assay. This effect was lost when the EMVs were depleted of miR‐126–5p. These results provide evidence that changes in miR expression and microvesicle packaging and transfer represent a mechanism of action of LXA4, which may be relevant in vascular biology and inflammation.—Codagnone, M., Recchiuti, A., Lanuti, P., Pierdomenico, A. M., Cianci, E., Patruno, S., Mari, V. C., Simiele, F., Di Tomo, P., Pandolfi, A., Romano, M. Lipoxin A4 stimulates endothelial miR‐126–5p expression and its transfer via microvesicles. FASEB J. 31, 1856–1866 (2017). www.fasebj.org